Ceramic-based surface treatments for metallic biomaterials - Mehta, Amrinder; Vasudev, Hitesh; Singh, Jashanpreet (Frontiers in Materials, 2025)
Ceramic-based surface treatments, including plasma spraying, sol-gel coatings, and hydroxyapatite (HAp) layers, have emerged as effective strategies for enhancing the functionality of metallic biomaterials in orthopedic and dental implants. These coatings enhance cellular adhesion, accelerate bone growth, enhance osseointegration, corrosion barriers, and wear, and help maintain the mechanical integrity of the implant during cyclic loading. Plasma spraying is currently used because it is inexpensive and can produce thick deposits, especially with HAp, which enhances implant osteoconductivity and corrosion resistance. Sol-gel techniques facilitate the deposition of a uniform, nanostructured coating at low temperature, which increases the homogeneity of the coating and bioactivity. Functionally graded finishes gradually transition in terms of composition or porosity between the metal interface and the outer surface, corresponding to the stiffness to minimize stress concentration without eliminating bioactive layers to encourage bone ingrowth. Antibacterial coatings of silver, copper, and zinc have proven effective in antimicrobial activity via a variety of mechanisms, providing extended protection against bacterial colonization of the implant surface. Despite their advantages, ceramic coatings face challenges, such as poor adhesion, delamination, and long-term durability under physiological loading. Ongoing research focuses on developing functionally graded, composite, and antibacterial coatings to improve the performance and longevity of biomedical implants. The optimization of the coating thickness, adhesion strength, and minimization of defects is crucial to maximize the protective effects and ensure the long-term success of ceramic-coated metallic implants in clinical applications.